Islet-like clusters derived from skeletal muscle-derived stem/progenitor cells for autologous transplantation to control type 1 diabetes in mice. (12th November 2018) - Lan, Kuo-Cheng; Wang, Ching-Chia; Yen, Yuan-Peng; Yang, Rong-Sen; Liu, Shing-Hwa; Chan, Ding-Cheng
Abstract: A population of muscle-derived stem/progenitor cells (MDSPCs) contained in skeletal muscle is responsible for muscle regeneration. MDSPCs from mouse muscle have been shown to be capable of differentiating into pancreatic islet-like cells. However, the potency of MDSPCs to differentiate into functional islet-like cluster remains to be confirmed. The therapeutic potential of autologous MDSPCs transplantation on type 1 diabetes still remains unclear. Here, we investigated a four-stage method to induce the differentiation of MDSPCs into insulin-producing clusters in vitro, and tested the autologous transplantation to control type 1 diabetes in mice. MDSPCs isolated from the skeletal muscles of mice possessed the ability to form islet-like clusters through several stages of differentiation. The expressions of pancreatic progenitor-related genes, insulin, and islet-related genes were significantly upregulated in islet-like clusters determined by the quantitative reverse transcription polymerase chain reaction. The autologous islet-like clusters transplantation effectively improved hyperglycaemia and glucose intolerance and increased the survival rate in streptozotocin-induced diabetic mice without the use of immunosuppressants. Taken together, these results provide evidence that MDSPCs from murine muscle tissues are capable of differentiating into insulin-producing clusters, which possess insulin-producing ability in vitro and in vivo, and have the potential for autologous transplantation to control type 1 diabetes.